Preparers’ Perceptions Towards Quarterly Financial Reporting in Malaysia (Malaysian Management Journal, 2004)
This study examines the perceptions of preparers of financial reports towards the issues surrounding corporate quarterly financial reporting in Malaysia. Questionnaires were mailed to chief financial officers of the Kuala Lumpur Stock Exchange (KLSE)1 listed companies, from whom 106 usable responses were gathered. The findings provide evidence that some preparers are not keen of the idea of quarterly reporting, despite the enforcement of the requirement. However, a majority of preparers are content with the current allowable reporting lag of two months, satisfied with the current content of the quarterly reports, and agree that management should at least discuss the quarterly results with the auditors. With respect to other matters, preparers expressed the view that the quarterly reports are reliable. However, there is also evidence that the first three quarterly reports are perceived to be less reliable than the fourth quarterly reports. The findings serve as an avenue for more research on quarterly financial reporting in Malaysia and other jurisdictions.